2020
DOI: 10.3390/su12219111
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fare-Free Public Transport: A Lesson from Frýdek-Místek (Czechia)

Abstract: The fare-free public transport policy (FFPT), the characteristic feature of which is abolishing fares in public transport, influences the transport system in favour of one means of transport. By joining the academic disputes over the outcomes of the FFPT policy, the aim of this paper is to understand the effects of the FFPT on overall mobility strategies and on the dynamics of the transport system where the policy is implemented. To do so, the paper is analysing a concrete example of the FFPT practice in Frýde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…What turned out to be crucial for the respondents was safety, travel-time (speed), and frequency. The order of the pyramid demonstrates the quality of the public transport service [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What turned out to be crucial for the respondents was safety, travel-time (speed), and frequency. The order of the pyramid demonstrates the quality of the public transport service [61].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, free public transport has an impact mainly on leisure activities [61]. These are usually regular trips in a relatively short time.…”
Section: Discussionmentioning
confidence: 99%
“…The participants also suggested that the service should be promoted to school and higher institution students by encouraging young people to use the service with their friends. Those who have experienced free public transport are more likely to have a positive perception towards the service, increasing their intention to use the bus [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a possibility that service providers have to bear the lost fare revenues. The FFPT policy has been observed to increase ridership in many cities [13,17]. In Frýdek-Místek, Czech Republic, the FFPT was implemented in selected zones to the advantage of the residents in the city, but with certain conditions [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation